PENGARUH INDIKATOR KEUANGAN TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA - Anisa Wiwid Rizkyana (2020)
This research is quantitative research that aims among other things to determine the effect of profitability, liquidity and leverage of the financial distress. The sample in this research is the mining companies listed in Indonesia Stock Exchange period 2017 - 2019. The sampling technique used in this research is purposive sampling method. The research sample of 27 companies. Testing the hypothesis in this study using logistic regression analysis with Eviews 10.0 program. The results of the test were obtained (1) Profitability does not affect the Financial Distress, (2) the Liquidity does not affect the Financial Distress, (3) the Leverage effect on Financial Distress